Struktur Komunitas Gastropoda pada Ekosistem Mangrove di Kelurahan Tosa Kecamatan Tidore Timur Kota Tidore Kepulauan - Samaun, Masrul; Damsiki, Nuraini Adung; Azis, Mahruf (Peneliti.net, 2026)
Gastropods are one of the mangrove animals utilized by humans as food because they have a high protein source. The mangrove ecosystem in Tosa Village has not been fully explored its potential, especially in terms of Gastropod diversity. Identification of the types of Gastropods in this area is important to provide baseline data and to provide input for the government and community in efforts to conserve and manage mangrove ecosystems sustainably. The study was conducted in August-October 2025, this type of research is quantitative description. The results obtained there are 18 species of gastropods. The diversity index of gastropods found in the mangrove ecosystem of Tosa Village is classified as moderate, the uniformity index at stations I and II is low category while at station III is moderate category, the dominance index is moderate category at station II while stations I and III have high dominance index values.